Composition and diverse differences of intestinal microbiota in ulcerative colitis patients - Zhu, Siying; Han, Muzhou; Liu, Simao; Fan, Liqiaona; Shi, Haiyun; Li, Peng (Frontiers in Cellular and Infection Microbiology, 2022)
Objective: To explore composition and diverse differences of intestinal microbiota in ulcerative colitis patients in the active and remission stage. Methods: Ulcerative colitis (UC) patients with the active and remissive stage and healthy controls were enrolled, and the stool samples were collected from September 2020 to June 2021. The diagnosis of UC patients was based on clinical, endoscopic, radiological and histological findings. of Intestinal microbiota composition was detected by 16S rRNA V3-V4 region sequencing and bioinformatics methods. Intestinal microbiota functional prediction was inferred using PICRUSt2. Results: We found that the richness and diversity of intestinal flora in UC patients was significantly lower that healthy controls. Beta diversity analysis revealed notable differences in the intestinal flora compositions among three groups, but there was no statistical difference in alpha diversity between the active and remission stage of UC patients. At the phylum level, the relative abundances of Proteobacteria and Patescibacteri were significantly higher, and Desulfobacterota and Verrucomicrobiota were lower in the active stage of UC patients compared to the HC group. Higher levels of potential pathogens and lower levels of butyrate-producing bacteria were also detected in the active stage of UC patients. LefSe analysis revealed that 71 bacterial taxa could serve as biomarkers, which including 26 of them at the genus level. In addition, network analysis showed that there was a positive correlation between Roseburia and Lachnospira. Functional predictions indicated that gene functions involving metabolism of some substances such as methane, lipopolysaccharide, geraniol and ansamycins, were significantly different among three groups. Conclusion: The richness and diversity of intestinal microbiota in UC was significantly different. Different bacterial taxa could be as biomarkers, which expanded our understanding of the relationship between intestinal microbiota microenvironment and UC in future.